2022
DOI: 10.1021/acsomega.2c03919
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Convection Nanofluid Flow with Heat Source and Chemical Reaction over an Inclined Irregular Surface

Abstract: Two-dimensional mixed convection radiative nanofluid flow along with the non-Darcy permeable medium across a wavy inclined surface are observed in the present analysis. The transformation of the plane surface from the wavy irregular surface is executed via coordinate alteration. The fluid flow has been evaluated under the outcomes of heat source, thermal radiation, and chemical reaction rate. The nonlinear system of partial differential equations is simplified into a class of dimensionless set of ordinary diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Zhang et al (2022) analyzed the flow of hybrid nanoliquid past a stretching surface and concluded that the fluid moved faster with higher values of the Darcy number, while the motion of fluid was retarded with an increase in the magnetic factor. Ojjela (2022) investigated the thermal transportation of hybrid nanofluid using alumina and silica nanoparticles and compared the results with established studies. The related analyses can be seen in Zabihi et al (2020a), Zabihi et al (2020b), Wahid et al (2020), Alhowaity et al (2022), Khan et al (2022b), andZabihi et al (2022).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2022) analyzed the flow of hybrid nanoliquid past a stretching surface and concluded that the fluid moved faster with higher values of the Darcy number, while the motion of fluid was retarded with an increase in the magnetic factor. Ojjela (2022) investigated the thermal transportation of hybrid nanofluid using alumina and silica nanoparticles and compared the results with established studies. The related analyses can be seen in Zabihi et al (2020a), Zabihi et al (2020b), Wahid et al (2020), Alhowaity et al (2022), Khan et al (2022b), andZabihi et al (2022).…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology is an exciting scientific discipline with numerous implementations that range from skincare brands, groceries, apparels, and home electronics to fuel catalysts, therapeutic approaches, and alternative resources. Construction activities, nanomachining of nanostructures, nanowires, nanosheets, water purifiers, and waste management are all examples of how nanotechnology is being used in advanced manufacturing and detoxification operations [15][16][17] . Their implementations are expanding to include "nanomedicine" by fusing nanostructures with microbial macromolecules or frameworks, "green technology" to improve sustainable development, and "renewable energy" to establish new methods of capturing, storing, and transferring energy.…”
Section: List Of Symbols V Umentioning
confidence: 99%
“…Haq et al . 20 investigated in the current analysis, 2D mixed convection radiative nanofluid flow and the non-Darcy porous medium with Chemical Reaction are seen across a wavy slope. Jamshed et al .…”
Section: Introductionmentioning
confidence: 99%